(untitled) (Journal of Economic Research & Business Administration, 2018)
Object of research. Object is to analyze the indicators of Kazakhstan in the «The Global Competitiveness Index», the rating of the World Economic Forum, to consider the measures of responsible state structures on improvement of indicators in the respective areas. Methodology of research. The research is classified as a desk research, the collection and processing of secondary information was performed, in particular, the data of the Report «The Global Competitiveness Index» of the World Economic Forum, data of the Committee on Statistics of the Ministry of National Economy of the Republic of Kazakhstan, and the data of the departmental ministries of the Republic of Kazakhstan were used to analyze the indicators. Interviews and public speeches of authorized persons published in the media were analyzed as a part of the study. Originality/value of research. In the strategically important state document, the «Digital Kazakhstan» program, which is a comprehensive document on the digitization of key sectors of the economy of country, the development of an innovative ecosystem and IT culture of the country, target positions of the Republic of Kazakhstan are listed as target indicators in the list of one of the most respectable ratings, the rating of World Economic Forum. This paper examines the actual position of Kazakhstan in the rating, the position in the «Innovations» group is considered in detail, and the measures taken and planned to improve current positions are consolidated – in the context of the country’s policy on digitalization of the economy and increasing the level of technological development, it is valuable for a rapid response and improvement of the situation. Conclusions. Results of the research showed that the evaluation of the current economic situation and competitiveness factors of the Republic of Kazakhstan in the rating of 2017-2018 demonstrates a significant deterioration of the country’s positions: the position of republic was dropped from the 53rd place (index – 4.41) to 57th place (index – 4.35). Main problems, according to opinion of experts, consist in the complicated access to financing, in the corruption and insufficient qualification of the working class. As for the leitmotif of the adopted course, the development of an innovative culture, the position of Kazakhstan in terms of innovative potential has dropped from the 59th to the 84th place in the world; also we can see the dropping by 11 positions on the «Ability to Innovations» indicator, from 73rd place to 84th. Specified estimates and the overall downgrade in rating of Kazakhstan are contrary to the implementation by KPI of the «Digital Kazakhstan» state program, which was undoubtedly reflected in the plan of activities of the departmental state agencies aimed at improving the positions in the rating, the action plan in consolidated form with intermediate results is also the subject of the current research and is presented in the paper.